A study on the regulation of D.N.A database in Malaysia / Fatin Athirah Anisan - Anisan, Fatin Athirah (2016)
There is no sufficient law which regulates the DNA database in Malaysia as compared to some other countries. The need of DNA database is becoming much crucial as new challenges and globalization takes place. Malaysia needs to have sufficient law regulating the DNA database to be used in the future. Currently there are cases which still being unsolved especially criminal cases due to the complicated method to do the DNA profiling. For the issue that exist to be resolved, a more stringent rule to be regulated on the DNA database and a clear procedure be established amongst those enforcement bodies involved be coordinated to ensure the privacy and safety of the public being protected. This paper aims to balance the need to collect DNA samples where direct evidence is lacking in violent crimes, versus the systematic collection of DNA from citizens who have committed acts such as petty crimes. The legal, ethical and social issues surrounding the proliferation of DNA collection and storage are explored, with a view to outlining the benefit of having the DNA database as tool of investigation purpose.